Sliding mode control subject to rice channel fading - Li, Jiarui; Niu, Yugang (IET control theory & applications, 2019)
In this study, the sliding mode control problem is investigated for a class of discrete-time systems with fading measurements. The channel fading is modelled as the Rice fading model to characterise the fading phenomenon via wireless sensor network. An integral-like sliding surface involving fading parameters is first constructed. And then, a sliding mode controller is designed by using fading measurements and channel parameters. It is shown that the state trajectories can be driven to the neighbourhood around the specified sliding surface and the stochastic stability with prescribed $\mathcal {H}_{∞ }$H∞ performance can be attained. Finally, a numerical example is provided.